2015 IEEE 11th International Conference on Power Electronics and Drive Systems 2015
DOI: 10.1109/peds.2015.7203391
|View full text |Cite
|
Sign up to set email alerts
|

Stator reference frame approach for DC injection-based stator resistance estimation in electric drives

Abstract: This work discusses an online stator resistance estimation method for synchronous machines. Multiple improvements are provided with respect to a similar method already been used for induction machines. The method is based on the temporary injection of a DC voltage in the machine phases during normal operation. The stator resistance estimation is obtained by means of the Ohm's law. The proposed scheme works entirely in the stator fixed reference frame, without the need of any machine parameter.The selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The stator resistance R s has to be known with good accuracy, to compute (11). A precise online tracking algorithm, based on a modified version of that proposed in [23], was…”
Section: Resultsmentioning
confidence: 99%
“…The stator resistance R s has to be known with good accuracy, to compute (11). A precise online tracking algorithm, based on a modified version of that proposed in [23], was…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm requires the a-priori knowledge of a precise and updated value of the stator resistance R s , which can be obtained by modern algorithms as for example those described in [19] and [20]. The training algorithm description is reported in Sect.…”
Section: Basics Of the Rbf-based Synr Motor Modelmentioning
confidence: 99%
“…The left-hand term of (19) is greater than zero for current phase angles below the correct one, and viceversa. Actually, it can been found that the mismatch computed by (19) is proportional to the required current phase angle modification. This is exploited by making the current phase modification proportional to the result of (19).…”
Section: The Mtpa Tracking Algorithmmentioning
confidence: 99%
See 2 more Smart Citations